Combating the Downward Spiral of Poverty: Lessons from Leviticus 25:35-22 and Its Implications for Modern Day Poverty Alleviation Efforts of the Church - Joseph Adasi-Bekoe (E-Journal of Humanities, Arts and Social Sciences)
Going downward, the spiral of poverty is common among the majority of the world’s poor whose lives are marked by the experience of being in and out of poverty. Relying on an exegesis of Leviticus 25.25-32, this article studies how the laws of Yahweh helped ancient and agrarian Israel prevent this common experience. The exegesis reveals that the text in Leviticus consists of four units, each describing a type of destitution that has the potential, if not handled carefully, to push a poor person down the downward spiral of poverty. The crisis that the laws anticipate appears to progress, first with a fellow Israelite who out of financial difficulty sold his land. The second envisages a person who survives on leased land from another Israelite. The third anticipates survival by means of debt enslavement to a fellow Israelite. The final law is aimed at helping the situation of debt enslavement to a non-Israelite. In all these cases of destitution, group identity, residence or location is important in determining the type of assistance and the people who qualify to assist. The laws call on all members of the community to act proactively to relieve neighbor’s poverty whenever one exhibits signs of poverty.